EFFECT OF LEARNING MODEL APPLICATION OF GUIDED LABORATORY INQUIRY TO LOGICAL THINKING ABILITY OF STUDENTS ON HEAT TO ELECTRICITY CONVERSION MATERIAL - Fauziah, Fitri; Suyanto, Eko; Wahyudi, Ismu; Herlina, Kartini (Universitas Tanjungpura, 2022)
This reseach aims to determine the application effect of guided inquiry laboratory model on students